Hepatitis C virus genotypes circulating in patients with chronic hepatitis C in Thailand and their responses to combined PEG-IFN and RBV therapy - Kattareeya Kumthip (2018)
Different genotypes of hepatitis C virus (HCV) are circulating in different areas of the world. In Thailand, distribution of HCV genotypes has been investigated mostly in the central area while the information in other regions is limited. This study aimed to determine the HCV genotypes circulating in chronic hepatitis C patients in Chiang Mai, Thailand and to investigate the response of different HCV genotypes to pegylated interferon (PEG-IFN) and ribavirin (RBV) treatment. Patients infected chronically with HCV were treated with PEG-IFN/RBV based on the standard regimens for each HCV genotype and followed up the patients until the end of treatment and 6 months afterward. Out of 158 patients, three major HCV genotypes and eight subtypes were identified. Genotype 3 was the most predominant at 54.5%, followed by genotypes 1 (31%) and 6 (14.5%). Among subtypes, 3a was the most prevalent subtype (45%), followed by 1b (18.4%), 1a and 6f (each at 12.6%), 3b (9.5%), and 6a, 6i, 6n (each at 0.63%). Patients with genotype 3 showed higher rate of responding to the treatment at 80.2% compared to genotypes 1 (73.5%) and 6f (65%). Additionally, patients with genotype 6f showed higher rate of relapsing (25%) compared to genotypes 1 and 3 (14.3% and 16.3%, respectively). In conclusion, this study reported multiple HCV genotypes circulated in Thai patients and the response of different HCV genotypes to PEG-IFN/RBV treatment. J. Med. Virol. 86:1360-1365, 2014. © 2014 Wiley Periodicals, Inc.